Analisis Disiplin Kerja Pada Era Fleksibilitas PT XYZ - Rizka Yuni Aulia; Susan Febriantina; Bayu Suhendry (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The implementation of work flecibility has become a corporatae strategy to adapt to technological advancements and changing work patterns however it also presents challenges in maintaining employee work discipline. This study aims to analyze the implementation of work discipline in the era of work flexibility at PT XYZ and to indentify the factors that hinder its effectiveness. The research employs a qualitative approach using interviews, observations, and documentation, with data analysis conducted using NVivo software. The findings indicate that work discipline is primaly based on performance outcomes and individual responsibility. The obtacles indentified include suboptimal work communication and unclear boundaries of work flexibility. This study provides implications for companies to strengthen policies and monitoring mechanisms to ensure that work flexibility remains aligned with work discipline. Keywords: Work Discipline,Work Flexibility, Nvivo